IMPROVEMENT OF SOCIAL PEDAGOGICAL ACTIVITY AS A PEDAGOGICAL PROBLEM - Rakhimova Feruza Najmiddinovna (Journals Park Publishing, 2024)
In this article, the improvement of social pedagogical activity, formation of cultural and educational abilities, social outlook, behavioral norms of the future generation in the activities of future pedagogic personnel, as well as the social development of the future generation in the educational system, social educational analysis, social phenomena and processes are discussed.
Keywords: socialization, education, training, cultural, educational, appreciation, multimedia.